Media Pembelajaran Bagi Siswa Autis Menurut Perspektif Islam - Az-Zahro, Fitri Charismaullah; Najikhah, Devista Khoirun; Bakar, M Yunus Abu (Jurnal Pendidikan Dasar dan Keguruan, 2024)
This research covers various educational media for children with special needs (autism), such as audiovisual aids and engaging images. These methods aim to support the interest and understanding of learning for children with special needs. Since children with special needs require different and more intensive learning approaches compared to typical children, and considering the Islamic perspective that does not discriminate based on ability, status, physical condition, or financial situation in accessing education, this journal aims to dispel the notion that children with special needs do not deserve the same educational opportunities as typical children. This journal is written using a literature review method, drawing from several journals with themes relevant to the chosen title.